Can Critical Teaching Foster Activism in this Time of Repression? - Shor, Ira (Radical teacher (Cambridge), 2019)
This Teaching Note provides a brief description of “participatory approaches with subject matters that are local, contemporary, contentious, co-developed, and legible” in a required composition course.